Comparison of intraoperative neuromonitoring accuracies and procedures associated with alarms in anterior versus posterior fusion for cervical spinal disorders: A prospective multi-institutional cohort study. Issue 49 (9th December 2022) - Wada, Kanichiro; Imagama, Shiro; Matsuyama, Yukihiro; Yoshida, Go; Ando, Kei; Kobayashi, Kazuyoshi; Machino, Masaaki; Kawabata, Shigenori; Iwasaki, Hiroshi; Funaba, Masahiro; Kanchiku, Tsukasa; Yamada, Kei; et al.
Abstract : A prospective multicenter cohort study. To clarify the differences in the accuracy of transcranial motor-evoked potentials (TcE-MEPs) and procedures associated with the alarms between cervical anterior spinal fusion (ASF) and posterior spinal fusion (PSF). Neurological complications after TcE-MEP alarms have been prevented by appropriate interventions for cervical degenerative disorders. The differences in the accuracy of TcE-MEPs and the timing of alarms between cervical ASF and PSF noted in the existing literature remain unclear. Patients (n = 415) who underwent cervical ASF (n = 171) or PSF (n = 244) at multiple institutions for cervical spondylotic myelopathy, ossification of the posterior longitudinal ligament, spinal injury, and others were analyzed. Neurological complications, TcE-MEP alarms defined as a decreased amplitude of ≤70% compared to the control waveform, interventions after alarms, and TcE-MEP results were compared between the 2 surgeries. The incidence of neurological complications was 1.2% in the ASF group and 2.0% in the PSF group, with no significant intergroup differences ( P -value was .493). Sensitivity, specificity, negative predictive value, and rate of rescue were 50.0%, 95.2%, 99.4%, and 1.8%, respectively, in the ASF group, and 80.0%, 90.9%, 99.5%, and 2.9%, respectively, in the PSF group. The accuracy of TcE-MEPs was not significantly different between the 2 groups ( P -value was .427 in sensitivity, .109 in specificity, and .674 in negative predictive value). The procedures associated with the alarms were decompression in 3 cases and distraction in 1 patient in the ASF group. The PSF group showed Tc-MEPs decreased during decompression, mounting rods, turning positions, and others. Most alarms went off during decompression in ASF, whereas various stages of the surgical procedures were associated with the alarms in PSF. There were no significant differences in the accuracy of TcE-MEPs between the 2 surgeries.